Influence of two high Temperature and Age on Some Productive and Egg Quality Traits in Laying Hens (Hisex Rrown) - Ali, Khasraw A.; Rashid, Saman A.M.; Ahmed, Shwan O. (Sulaimani Journal for Pure and Applied Sciences, 2004)
Influence of two different temperatures(2l.6 and 25.l C )and five age groups (23-26,27-30,31-34, 35-38 and 39-42 weeks of age) on body weight, feed consumption, egg production, egg weight, yolk weight, albumen weight, shell weight, shell thickness and egg shape index were studied. Results indicate that temperature effects was significant only on egg production (p<0.05)^ Age effect, ot the other hand, was significant for trody weight, feed consumption, egg production, egg weight and yolk weight. Highest production was obtained at age o{ 27-34 weeks.
Keywords: laying hens; temperature; age; egg quality